What is it important to know when using the critical velocity concept in swimming training? - Pelayo, P.; Alberty, M.; Sidney, M.; Potdevin, F.; Anddekerle, J. (1st International Scientific Conference of Aquatic Space Activities, 2008)
Because swimming coaches and scientists need to define accurately exercise intensity domains to optimize and evaluate aerobic and severe swimming training programs, the purposes of this review are to: 1. Review the recent studies conducted on the assessment and using of the Critical Swimming Speed (CSS) in order to well define the intensity domains and their boundaries. 2. Verify whether the speed corresponding to the slope of the distance-time relationship (Sd-t) in swimming is sustainable and represents the boundary between the heavy and severe intensity domains in swimming. 3. Assess whether intermittent swims at Sd-t are tolerable and induce a physiological and psychological stress.